Testing some psychometric properties of the Italian version of the Skin Cancer Index: A questionnaire for measuring quality of life in patients with non-melanoma skin cancer - Samela, Tonia; Raimondi, Giulia; Sampogna, Francesca; Ricci, Francesco; Fania, Luca; Mastroeni, Simona; Fusari, Roberta; Salcedo, Nidia Melo; Dattolo, Anna; Papanikolaou, Elena Sofia; Abeni, Damiano (Frontiers in Psychology, 2022)
Objectives: Non-melanoma skin cancers (NMSC) include two main types: basal cell carcinoma (BCC) and cutaneous squamous cell carcinoma (cSCC). Generic Health Related Quality of Life (HRQoL) instruments revealed little to no HRQoL impairment in NMSC patients. Instead, the use of specific skin disease HRQoL tools contradicted those observations. For example, the Skin Cancer Index (SCI) was suggested as a validated instrument for the evaluation of the impact of skin cancers on HRQoL, and has already been validated in several languages, but not in Italian. The aim of this study is to validate the Italian version of the SCI questionnaire in a large sample of NMSC patients. Methods: This is a cross-sectional, single-center, observational study. Firstly, different factor models proposed in the literature were compared and the model with the best fit was idenfitied. Secondly, the psychometric properties of the SCI, convergent validity and reliability, were evaluated. Results: The sample was composed of 371 NMSC patients. The factor analysis revealed that a revised version of the original model had the best fit (χ2(df = 85) = 354.53, P < 0.001, RMSEA = 0.09, CFI = 0.98, TLI = 0.97, SRMR = 0.03). The SCI had satisfactory internal consistency for all subscales (Emotional subscale: ordinal alpha = 0.95; Social subscale: ordinal alpha = 0.94; Appearance subscale: ordinal alpha = 0.94). The convergent validity with Skindex-17 psychosocial subscale was adequate for all the SCI subscales (Emotional Subscale: rho= -0.50; Social Subscale: rho= -0.54; Appearance subscale: rho=-0.44; Total Skin Cancer Index: rho=-0.56; P<0.001). Conclusion: The Italian version of the SCI may be considered a reliable and valid tool for assessing specific HRQoL in NMSC patients.